Financial reporting quality of privately held firms: evidence from private corporations versus limited companies. Issue 5 (3rd September 2022) - Baik, Bok; Han, Seung-Youb; Kim, Bong Hwan; Oh, Seungbin
ABSTRACT: In this paper, we examine whether requirements to disclose audited financial statements enhance financial reporting quality of privately held firms. Unlike U.S. private firms, private corporations in Korea are required to prepare and disclose audited financial statements. While limited companies, another type of Korean private firms, are almost identical to private corporations in economic substance, they are exempt from reporting requirements to disclose audited financial statements. Using this unique institutional environment in Korea for the period of 2007–2012, we investigate the effect of audit and disclosure requirements on financial reporting quality and find that such requirements enhance financial reporting quality of private companies. Our findings shed light on the economic consequences of mandatory disclosure of audited financial statements and should be of interest to academics and regulators as we evidence the effects of audit and disclosure requirements on financial reporting quality outside of public firms.